Lipid Peroxidation Product 4-Hydroxy-trans-2-nonenal Causes Endothelial Activation by Inducing Endoplasmic Reticulum Stress - Vladykovskaya, Elena (American Society for Biochemistry and Molecular Biology, 2012)
Lipid peroxidation products, such as 4-hydroxy-trans-2-nonenal (HNE), cause endothelial activation, and they increase the adhesion of the endothelium to circulating leukocytes. Nevertheless, the mechanisms underlying these effects remain unclear. We observed that in HNE-treated human umbilical vein endothelial cells, some of the protein-HNE adducts colocalize with the endoplasmic reticulum (ER) and that HNE forms covalent adducts with several ER chaperones that assist in protein folding. We also found that at concentrations that did not induce apoptosis or necrosis, HNE activated the unfolded protein response, leading to an increase in XBP-1 splicing, phosphorylation of protein kinase-like ER kinase and eukaryotic translation initiation factor 2α, and the induction of ATF3 and ATF4. This increase in eukaryotic translation initiation factor 2α phosphorylation was prevented by transfection with protein kinase-like ER kinase siRNA. Treatment with HNE increased the expression of the ER chaperones, GRP78 and HERP. Exposure to HNE led to a depletion of reduced glutathione and an increase in the production of reactive oxygen species (ROS); however, glutathione depletion and ROS production by tert-butyl-hydroperoxide did not trigger the unfolded protein response. Pretreatment with a chemical chaperone, phenylbutyric acid, or adenoviral transfection with ATF6 attenuated HNE-induced monocyte adhesion and IL-8 induction. Moreover, phenylbutyric acid and taurine-conjugated ursodeoxycholic acid attenuated HNE-induced leukocyte rolling and their firm adhesion to the endothelium in rat cremaster muscle. These data suggest that endothelial activation by HNE is mediated in part by ER stress, induced by mechanisms independent of ROS production or glutathione depletion. The induction of ER stress may be a significant cause of vascular inflammation induced by products of oxidized lipids.